2013
DOI: 10.1107/s0021889813005268
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive reconstruction method for three-dimensional orientation imaging

Abstract: An adaptive orientation reconstruction algorithm is developed for near‐field high‐energy X‐ray diffraction microscopy. When combined with a spatially adaptive extension the algorithm results in a factor of 10–1000 speed‐up over the existing forward modeling reconstruction method while preserving most of the spatial and orientation resolution characteristics. Tests of the reconstruction code based on simulated structures and real data on a complex microstructure are presented. Simulated structures include intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
97
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(103 citation statements)
references
References 34 publications
0
97
0
Order By: Relevance
“…33 Reconstructed voxels from each plane were integrated into 3D volumes representing the preand post-shocked orientation fields. These states were reconstructed using equilateral triangular voxels of sidewidth 5.6 lm and 2.8 lm, respectively.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Reconstructed voxels from each plane were integrated into 3D volumes representing the preand post-shocked orientation fields. These states were reconstructed using equilateral triangular voxels of sidewidth 5.6 lm and 2.8 lm, respectively.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…23 Novel modeling and simulation efforts have confirmed that grain boundaries with different character behave differently under high rate dynamic compression 15,24 and demonstrated success in elucidating the void growth regime. 31 In this work, we use synchrotron-based near-field High Energy Diffraction Microscopy (nf-HEDM) 32,33 to map the microstructure of a mm 3 -sized, well-annealed copper sample. The specimen was shock loaded using an experimental setup tuned to form micro-scale voids.…”
Section: Introductionmentioning
confidence: 99%
“…Forward modelling has been successfully applied in many types of diffraction-based experiments, including the indexing of three-dimensional X-ray diffraction microscopy data (Li & Suter, 2013;Schmidt, 2014), EBSD data (Chen et al, 2015) and electron channelling patterns . Any forward-modelling method requires a discretization of SOð3Þ.…”
Section: Previous Workmentioning
confidence: 99%
“…To date, this collection of methods have largely been thought of as individual techniques, including far field HEDM (ff-HEDM) to measure the average elastic strain tensor of individual grains (stress tensor with known elastic stiffness matrix) [24][25][26][27] and near field HEDM (nf-HEDM) to map the structure and local crystallographic orientation within and between grains. 21,28,29 While the individual techniques are valuable on their own, the concurrent application of nf-HEDM, ff-HEDM, and others such as absorption micro-computed tomography (µ-CT) for mapping the structure of voids, cracks, and/or inclusions which may be present, 30 can provide incredibly rich datasets from which to develop and validate microstructure sensitive materials models.…”
Section: Introductionmentioning
confidence: 99%